Corporate Venture Capital as a Window on New Technologies: Implications for the Performance of Corporate Investors When Acquiring Startups - Benson, David; Ziedonis, Rosemarie H. (Organization Science, 2009)
Gaining a “window” on new technologies is a prominent motive for corporate venture capital (CVC) investing. Recent studies suggest that information gained through CVC-related activities can improve the internal R&D productivity of established firms. This study investigates an alternative means by which information gained through CVC investing could improve firm performance—by increasing the returns to corporate investors when acquiring startups. We provide new insights based on an event study of the returns to 34 corporate investors from acquiring 242 technology startups. Consistent with predictions drawn from the absorptive capacity literature, we find that the effect of CVC investing on acquisition performance hinges critically on the strength of the acquirer's internal knowledge base: as CVC investments increase relative to an acquirer's total R&D expenditures, acquisition performance improves at a diminishing rate. We also find that firms consistently engaged in venture financing earn greater returns when acquiring startups than do firms with more sporadic patterns of investing, even controlling for firm profitability, size, and acquisition experience. These findings suggest that corporate investors systematically differ in their abilities to derive added benefits from external venturing as acquirers of entrepreneurial firms.